2012
DOI: 10.1038/nrneph.2012.246
|View full text |Cite|
|
Sign up to set email alerts
|

Hyponatraemia: more than just a marker of disease severity?

Abstract: Hyponatraemia--the most common serum electrolyte disorder--has also emerged as an important marker of the severity and prognosis of important diseases such as heart failure and cirrhosis. Acute hyponatraemia can cause severe encephalopathy, but the rapid correction of chronic hyponatraemia can also profoundly impair brain function and even cause death. With the expanding elderly population and the increased prevalence of hyponatraemia in this segment of society, prospective studies are needed to examine whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 160 publications
2
73
1
5
Order By: Relevance
“…1,3,4 A postulated mechanism of hyponatremia influencing outcome also in neurointensive care could be its relation to an increased nonosmotic release of AVP caused by the overstimulation of the neurohumoral axis or by baroreceptor failure in elderly patients leading to cerebral hypoperfusion. 11,28 After severe neurotrauma such as ICH, increased intracranial pressures and cerebral hypoperfusion may even aggravate secondary brain injury. Assuming that these mechanisms play a role in patients with ICH, increased AVP levels themselves could contribute to a reduced tolerance to cerebral hypoxia.…”
Section: May 2014mentioning
confidence: 99%
“…1,3,4 A postulated mechanism of hyponatremia influencing outcome also in neurointensive care could be its relation to an increased nonosmotic release of AVP caused by the overstimulation of the neurohumoral axis or by baroreceptor failure in elderly patients leading to cerebral hypoperfusion. 11,28 After severe neurotrauma such as ICH, increased intracranial pressures and cerebral hypoperfusion may even aggravate secondary brain injury. Assuming that these mechanisms play a role in patients with ICH, increased AVP levels themselves could contribute to a reduced tolerance to cerebral hypoxia.…”
Section: May 2014mentioning
confidence: 99%
“…Whether hyponatraemia in a patient with cancer is merely a marker of poor prognosis or whether its presence may alter the patient's quality of life has not been definitively answered, but there is increasing evidence that hyponatraemia can no longer be considered just a biochemical ‘bystander’ in the ill patient 19. A systematic diagnostic approach is necessary to determine the specific aetiology of a patient's hyponatraemia.…”
Section: Considerations Regarding Hyponatraemia and Siadh Managementmentioning
confidence: 99%
“…20,21 Multiple studies have found an association between hyponatremia in ADHF and adverse effects, including days hospitalized and mortality. 20,22 One major factor in the development of hyponatremia in ADHF is the nonosmotic secretion of arginine vasopressin, which in addition to its vasopressive effects, acts as an antidiuretic in the kidney through stimulation of aquaporin-2 in the renal collecting ducts. Arginine vasopressin acts through three different but related receptors known as V1a, V1b and V2.…”
Section: Tolvaptanmentioning
confidence: 99%
“…Hemodynamic determinations were taken at baseline and during the infusion period at frequent intervals (0.5, 2, 4, 6, 8, and 20 hours), and during the washout period (21,22, and 24 hours). The peak PCWP decreased rapidly in the serelaxin group, and was significantly lower during the intervals from 0-8 hours.…”
mentioning
confidence: 99%